Analisis External Environment Pada PT. Indofood Sukses Makmur Tbk - Jhohari Jhohari; Raihan Raihan; Sahat Juliwan Tarihoran; Kevin Jonay Lie; Gladys Christiani (Universitas 17 Agustus 1945, 2022)
The external environment is one way for companies to know the opportunities and threats they will face. This analysis was carried out with the aim of knowing what influences PT. Indofood in their external environment section. Qualitative data is the method used in this study. From the results of this analysis it is revealed how the external environment of the Indofood company is.